A computational analysis of potential aortic dilation induced by the hemodynamic effects of bicuspid aortic valve phenotypes. (June 2022) - Hou, Qianwen; Tao, Keyi; Du, Tianming; Wei, Hongge; Zhang, Honghui; Chen, Shiliang; Pan, Youlian; Qiao, Aike
Highlights: The differences in the development of aortic dilation induced by BAV phenotypes remains unclear. We provided a controlled environment consisting of the same non-dilated aorta subjected to the different Type-1BAV phenotypes, and compared the early effect of different phenotypes of BAV on aortic hemodynamics. The real aorta has the specific curvature, which has an impact on the blood flow pattern. Therefore, we adopted a healthy personalized aortic model and added coronary artery. In this study, a steady-state CFD simulation is performed and the blood was set to be k-epsilon turbulent flow mode, which has a great impact on the results at peak systolic. Abstract: Background and objectives: The bicuspid aortic valve (BAV) is a major risk factor for the progression of aortic dilation (AD) because of the induced abnormal blood flow environment in aorta. The differences in the development of AD induced by BAV phenotypes remains unclear. Therefore, the objective of this study was to assess the potential locations of AD induced by different phenotypes of BAV. The different effects of opening orifice area and leaflet orientation on ascending aortic hemodynamics in Type-1 BAV was investigated by means of numerical simulation. Methods: Finite element dynamic analysis was performed on tricuspid aortic valve (TAV) and BAV models to simulate the motion of the leaflets and obtain the geometrical characteristics of AV at peak systole as a reference, which were used for aortic models. Then, four sets of aortic fluid models were designed according to the leaflet fusion types [TAV; BAV (left-right-coronary cusp fusion, LR; right-non-coronary cusp fusion, RN; left-non-coronary cusp fusion, LN)], and the computational fluid dynamics method was applied to compare the hemodynamic differences within the aorta at peak systole. Results: The maximum opening area of BAV was significantly reduced, resulting in alterations in aortic hemodynamics compared with TAV. The velocity streamlines were essentially parallel to the aortic wall in TAV. The average pressure and wall shear stress in aorta tend to be stable. In contrary, the eccentricity of BAV orifice jet resulted in high-velocity flow directed toward the ascending aorta (AA) wall and aortic arch for LR and LN; RN features an asymmetrical velocity distribution toward the outer bend of the middle AA, and eccentric flow tends to impact the distal AA. As the flow angle is associated with distinct flow impingement locations, different degrees of WSS and pressure concentration occur along the aortic wall from the AA to the aortic arch in three BAV types. Conclusions: The BAV morphotype affects the aortic hemodynamics, and the abnormal blood flow associated with BAV may play a role in AD. The different BAV phenotypes determine the direction of blood flow jet and change the expression of dilation. LR is likely to cause dilation of the tubular AA; RN results in dilation of the middle AA to proximal aortic arch; and LN causes an increased incidence of the tubular AA and the proximal aortic arch.